Optimasi Perencanaan Keuntungan Produksi pada Pengolahan Rendang di Perusahaan “Rendang Erika” Payakumbuh - Deswani Panggabean; Masrul Djalal; Santosa (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2014)
Rendang is a traditional Minangkabau food. Rendang is generally made of meat, coconut milk and seasoning. Generally rendang semi-wet, but now it has been modified into a dry rendang. Dry rendang widely produced at Payakumbuh, West Sumatra Province. This research was conducted in July to August 2013 at Company